The stabilized rammed earth building technique and its use in Australia (REVISTA NODO, 2019)
The building technique known as rammed earth has been used in Australian civil construction for decades. This practice, used in various regions of Australia, has brought with it important technical improvements to the execution of Stabilized Rammed Earth (SRE) buildings. This study highlights some of those advances in terms of construction details, composition, special cares during execution, the use of formwork, and construction pathologies, however, these can be considered and incorporated into the traditional (unstabilized) rammed earth technique. This article aims to inform and update professionals and students about the evolving technology of using earth as the main building material, providing relevant information about its contemporary production. It aims to share design and building insights that may enrich the knowledge around the limits and needs of the SRE, and to contribute to the research of its productive chain, from the supply of raw materials to maintenance. By acquiring the knowledge produced so far regarding this technique, it is possible to break free from preconceptions and misconceptions about the earth as a building material. Part of this knowledge is hereby analyzed and shared, to contribute of the dissemination of the use of the Stabilised Rammed Earth technique.
Keywords: earth building; stabilized rammed earth; contemporary Australian architecture; development of building techniques